2020
DOI: 10.1128/msphere.00877-19
|View full text |Cite
|
Sign up to set email alerts
|

The Secreted Acid Phosphatase Domain-Containing GRA44 from Toxoplasma gondii Is Required for c-Myc Induction in Infected Cells

Abstract: During host cell invasion, the eukaryotic pathogen Toxoplasma gondii forms a parasitophorous vacuole to safely reside within the cell, while it is partitioned from host cell defense mechanisms. From within this safe niche, parasites sabotage multiple host cell systems, including gene expression, apoptosis, and intracellular immune recognition, by secreting a large arsenal of effector proteins. Many parasite proteins studied for active host cell manipulative interactions have been kinases. The translocation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…While this work was in progress, we learned of similar studies by Blakely et al, who also found that GRA44 associates with MYR1 and is necessary for efficient c-Myc upregulation during infection (40). The latter authors used a knockdown approach to study GRA44 and saw a more dramatic impact of GRA44 loss on parasite growth than we and others (30) observed for the GRA44 knockout; this might indicate that compensatory changes were selected for during the prolonged selection necessary to generate and expand our knockout clone, as was reported for AMA1 knockouts, which showed a dramatic upregulation of the paralogue, AMA2 (41).…”
Section: Discussionmentioning
confidence: 68%
“…While this work was in progress, we learned of similar studies by Blakely et al, who also found that GRA44 associates with MYR1 and is necessary for efficient c-Myc upregulation during infection (40). The latter authors used a knockdown approach to study GRA44 and saw a more dramatic impact of GRA44 loss on parasite growth than we and others (30) observed for the GRA44 knockout; this might indicate that compensatory changes were selected for during the prolonged selection necessary to generate and expand our knockout clone, as was reported for AMA1 knockouts, which showed a dramatic upregulation of the paralogue, AMA2 (41).…”
Section: Discussionmentioning
confidence: 68%
“…These results demonstrate that GRA45 plays a critical role in the correct trafficking of PVM-integrated or -associated GRAs after exocytosis of dense granules. GRA44, as the known GRA45 interaction partner, has no predicted hydrophobic domain but localizes to the PV 49 , 80 . In contrast to the localization changing from PVM to the PV lumen for above GRAs, GRA44 resided inside the cytosol of Δ gra45 parasites instead of being secreted into the PV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The coverslips were incubated with anti-SAG1 antibodies and anti-HA antibodies or anti-Ty antibodies at 4°C overnight. To observe the localization of GRA44, HFFs infected with wild-type, Δ gra45 or Δ gra45 + GRA45HA strains transiently expressing GRA44-Myc 80 for 20 h were fixed, permeabilized and blocked as described above followed by incubation with anti-Myc antibodies at 4°C overnight. After incubating with Alexa Fluor 488/594 secondary antibodies and DAPI, the coverslips were mounted with Vecta-Shield mounting oil and the microscopy was performed with NIS-Elements software (Nikon) and a digital camera (CoolSNAP EZ; Roper Scientific) connected to an inverted fluorescence microscope (Eclipse Ti-S; Nikon) and either phase contrast or DIC imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Exported effectors such as GRA16 and TgIST have been elegantly characterized and shown to influence host cell signaling in profound ways that benefit the intracellular development of the parasite [23,26,27]. Several effectors exported from the parasitophorous vacuole have been described apart from those explored in this study [9,28,29,46], while the list of proteins necessary for the export of these proteins has also been growing, including an acid phosphatase domain-containing protein in GRA44 [21,[47][48][49]. Cygan et.…”
Section: Plos Pathogensmentioning
confidence: 94%